2006
DOI: 10.1007/s00467-006-0039-0
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress, inflammation and early cardiovascular damage in children with chronic renal failure

Abstract: The relationship between inflammation, oxidant stress and cardiovascular damage in children with chronic renal failure (CRF) has not previously been investigated. The aim of this study was to investigate markers of oxidative stress, inflammation and early cardiovascular abnormalities. Therefore, erythrocyte superoxide dismutase (SOD) and catalase (CAT) activities; blood glutathione (GSH) and serum malondialdehyde (MDA) levels; C-reactive protein (CRP) and proinflammatory cytokines (IL-6, TNF-alpha,); and left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
39
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 32 publications
2
39
1
1
Order By: Relevance
“…Studies have reported that catalase is a major intracellular antioxidant enzyme. 6,26,27 In our study, catalase activity was found to be unimportantl in fascioliasis since no statistically significant difference was available between patients and control groups (p>0.05). Rehim WM et al in their study have reported that antioxidative support treatment may be helpful in elimination of F hepatica.…”
Section: Discussionmentioning
confidence: 48%
“…Studies have reported that catalase is a major intracellular antioxidant enzyme. 6,26,27 In our study, catalase activity was found to be unimportantl in fascioliasis since no statistically significant difference was available between patients and control groups (p>0.05). Rehim WM et al in their study have reported that antioxidative support treatment may be helpful in elimination of F hepatica.…”
Section: Discussionmentioning
confidence: 48%
“…There was a highly significant difference between cases and controls as regard CAT, SOD, GPX; SOD was indirectly correlated with CAT and directly correlated with GPX. Studies have reported that CAT is a major intracellular antioxidant enzyme (Aslan et al 2007;Simsek et al 2006) although, Karsen et al (2011) reported that CAT activity was found to be unimportant in fascioliasis since no statistically significant difference was available between patients and control groups (Ece et al 2006). LPO is an ongoing physiological process, but several lines of evidence have suggested an important role for peroxidation in the pathogenesis of several parasitic diseases (Erel et al 1997;Karsen et al 2011;Oliveira and Cechini 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the enhanced inflammatory state were the elevated C-reactive protein levels in a majority of the patients whom we studied (9) and that the degree of inflammation correlated with the number of years that patients lived with ESRD (dialysis vintage). A recent study showed that there is increased oxidant stress and early cardiovascular damage in children with various stages of renal insufficiency, although the cohort included only a small number of patients who were receiving dialysis (10). On the basis of our previous studies, we decided to perform a pilot study to assess the anti-inflammatory capacity of daily, low-dosage aspirin on serum cytokine concentrations in children who were receiving maintenance HD or peritoneal dialysis (PD).…”
mentioning
confidence: 99%